PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT DALAM UPAYA MEMENUHI KEPUASAN PELANGGAN TERHADAP LAYANAN PESAN ANTAR PIZZA (Studi Kasus pada S2 Pizza, Bali) - Cahaya Tyasdela, A.A. Putri; Satriawan, I Ketut; Suryawan Wiranatha, A.A.P.Agung (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
Improvement and development of the quality of services such as delivery order at the restaurant is now a public concern. The purpose of this study are: (1) to determine the attributes that necessitated by the customers about  delivery order service; (2) to measure the level of customers interest on the quality of delivery order service and (3) to measure the level of customers satisfaction on the quality of delivery order service. This study used Quality Function Deployment (QFD) method. The results showed that there are 21 attributes of consumer interests necessitated by the consumer with a very important criterion. The highest consumer interest was attributes of food hygiene and beverages. The level of customer satisfaction with all consumer interest attributes of S2 Pizza were varying from usual/neutral to very satisfied. S2 Pizza needs to gives special attention to the attributes of customers complaint response, the identity of the restaurant's name on the shirt, jacket, and vehicles, and attributes of employees appearances of (cleanliness and tidiness).
Keywords: 66